2013
DOI: 10.1089/chi.2012.0028
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Young Children with Autism Spectrum Disorders: Prevalence and Associated Factors

Abstract: Children with ASD are at risk for overweight and obesity, and children with autistic disorder are at greater risk for weight problems than children with Asperger's disorder/PDD-NOS. Further research is needed to identify factors related to overweight in children with ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
86
3
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 23 publications
9
86
3
3
Order By: Relevance
“…These prevalence estimates are consistent with recently reported estimates based on measured height and weight in people with ASDs. 45,70 For example, Broder-Fingert et al 45 found significantly elevated rates of overweight (exclusive of obesity) and obese weight status among children with Asperger syndrome and autism compared with control children in every age category (2-5, 6-11, 12-15, and 16-20 years). In our analyses, prevalence of overweight and obesity was consistently higher for ASDs, except among children with ASDs ages 6-11 years.…”
Section: Discussionmentioning
confidence: 99%
“…These prevalence estimates are consistent with recently reported estimates based on measured height and weight in people with ASDs. 45,70 For example, Broder-Fingert et al 45 found significantly elevated rates of overweight (exclusive of obesity) and obese weight status among children with Asperger syndrome and autism compared with control children in every age category (2-5, 6-11, 12-15, and 16-20 years). In our analyses, prevalence of overweight and obesity was consistently higher for ASDs, except among children with ASDs ages 6-11 years.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is estimated to have a prevalence rate of 30% in children with ASD compared to 24% of their typically developing peers [11,12]. Even more alarming, obesity continues into adulthood for those with ASD at a rate of 42% [13] which can contribute to serious health problems such as depression, diabetes mellitus, sleep apnea, and cardiovascular disease as well as social problems such as isolation, stigma, discrimination, and low selfesteem [11,12]. Furthermore, the economic costs of obesity have been estimated to be nearly 10% of total medical expenditures resulting in increased lifetime costs [13].…”
Section: Food Selectivity In Obese Adolescents With Autism Spectrum Dmentioning
confidence: 99%
“…Even more alarming, obesity continues into adulthood for those with ASD at a rate of 42% [13] which can contribute to serious health problems such as depression, diabetes mellitus, sleep apnea, and cardiovascular disease as well as social problems such as isolation, stigma, discrimination, and low selfesteem [11,12]. Furthermore, the economic costs of obesity have been estimated to be nearly 10% of total medical expenditures resulting in increased lifetime costs [13]. Rates of obesity are increasing at younger ages producing health complications earlier and may require interventions at younger ages [13].…”
Section: Food Selectivity In Obese Adolescents With Autism Spectrum Dmentioning
confidence: 99%
See 2 more Smart Citations